Indigenous peoples and the Green Climate Fund - Magata, Helen Biangalen; de Chavez, Raymond; Martone, Francesco; Angarova, Galina; Riamit, Stanley Kimaren Ole; Cunningham, Eileen Mairena; Tripura, Mrinal Kanti (Baguio City Tebtebba Foundation, 2017)
This publication was conceived to consolidate the reports, letters and briefing notes of indigenous peoples' engagement with the GCF thus far. It also aims to celebrate the achievements and account for the challenges and opportunities that indigenous peoples face in the Green Climate Fund.
Part I: Indigenous peoples' key issues and proposals to the green climate fund -- Part II: Capacitating indigenous peoples on the Green Climate fund.
In English.
Keywords: Indigenous peoples -- Social conditions; Indigenous peoples -- Economic conditions; Climatic changes -- Government policy